PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS PROJECT-BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN SENI DAN KREATIVITAS SISWA KELAS SATU SD - Sri Wahyuni; Eka Titi Andaryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted due to the low artistic skills and creativity of early grade students in grade I of Elementary School. Initial observations conducted at the pre-development stage showed that many students had difficulty in expressing ideas visually and lacked originality in their artwork, as well as the lack of learning media that could integrate interactive technology with real project experiences at the elementary level. This research took 28 grade I elementary school students as subjects. This research aims to: (1) describe the process of developing PjBL-based Interactive E-Modules, (2) describe the level of feasibility (validity and practicality) of PjBL-based Interactive E-Modules, and (3) describe the results of testing the effectiveness of PjBL-based Interactive E-Modules in art learning to improve students' artistic skills and creativity. The research methodology used a mix methods method. Research Results: (a) The process of developing PjBL-based Interactive E-Modules follows the PjBL steps: Syntax 1: Determining Basic Questions. Syntax 2: Preparing Project Planning (Project Design). Syntax 3: Schedule Preparation. Syntax 4: Implementation (Monitoring Students). Syntax 5: Assess the Outcome. Syntax 6: Evaluate the Experience. (b) The developed Interactive E-Module received a very good validation score from material and media experts, and was deemed very good by teachers and students. (c) The effectiveness test results showed a 61% increase in average art skills scores and a 30% increase in average creativity scores compared to before the module was used. The implementation of the Project-Based Learning (PjBL)-based Interactive E-Module in art learning created an active, digital, and product-oriented learning environment, thereby increasing students' motivation, participation, and artistic skill achievement. This study concluded that the Project-Based Learning (PjBL)-based Interactive E-Module was effective in improving artistic skills and creativity in first-grade elementary school students.